Growth Strategies and Performance of Commercial Banks in Nairobi County, Kenya - Mutua, Miriam Muthoki; Kori, Blandina (Journal of Strategic Management, 2022)
Changing trends globally and customers’ expectations are forcing banks to search for new ways of income generation. Growth strategies often play a vital role in a business’s management as it allows a company to choose a direction of action and determine how to achieve its goals. The general objective of the study was to determine the effect of growth strategies on performance of commercial banks in Nairobi County, Kenya. The specific objective was to examine effect of diversification strategy on performance of Commercial banks in Nairobi County, Kenya. The study was anchored on porters’ theory of competitive advantage and modern portfolio theory. This study adopted a descriptive research design. The target population was 794 bank staff from 39 commercial banks in Nairobi County. Stratified random sampling was used to sample 238 bank staff. The study used primary data which was collected using questionnaires. A pilot study was conducted with 24 respondents representing 10% of the sample. The research used content validity. Cronbach’s Alpha Coefficient method was used to measure questionnaire reliability. Ethics of confidentiality, anonymity, no harm to the respondents’, and voluntarily participation was adhered to strictly when collecting data. Quantitative data was analyzed using descriptive and inferential statistics and tabulated. The findings showed that diversification enables the bank to leverage its resources effectively and that diversification enhances risk minimization in the banks’ investments. It was also found that diversification influences good decision making on profitable investments. In addition, the study established that risk mitigation strategies are reinforced through diversification. The study concludes that diversification strategy has a positive and significant effect on the performance of commercial banks in Nairobi County, Kenya. This study recommends that the banks should adopt diversification in their operations through use of technological advancements and other aspects such as innovation and benchmarking strategies to realize full benefits of diversification. Further, the management of commercial banks in Nairobi County should formulate and implement effective strategies to enhance regional, national and new customer segments development. Key words: Growth Strategies, Diversification Strategy, Organizational Performance